Особенности генетической структуры периферийных популяций малярийного комара Anopheles messeae (Diptera, Culicidae) - Шуваликов, Б.В. (Вестник зоологии, 1982)
Inversion polymorphism in Anopheles messae populations of the Ukraine is described.. Sharp inversion frequences observed in differentsamples can be explained neither by climatic factors effect, nor by remoteness from the species range centre. Hereditary uni- form groups are recognized within the studied area, which suggests discrete species organization.